CORKSCREW1 defines a novel mechanism of domain specification in the maize shoot. - Alexander, D; Mellor, E; Langdale, J (2005)
In higher plants, determinate leaf primordia arise in regular patterns on the flanks of the indeterminate shoot apical meristem (SAM). The acquisition of leaf form is then a gradual process, involving the specification and growth of distinct domains within the three leaf axes. The recessive corkscrew1 (cks1) mutation of maize (Zea mays) disrupts both leaf initiation patterns in the SAM and domain specification within the mediolateral and proximodistal leaf axes. Specifically, cks1 mutant leaves exhibit multiple midribs and leaf sheath tissue differentiates in the blade domain. Such perturbations are a common feature of maize mutants that ectopically accumulate KNOTTED1-like homeobox (KNOX) proteins in leaf tissue. Consistent with this observation, at least two knox genes are ectopically expressed in cks1 mutant leaves. However, ectopic KNOX proteins cannot be detected. We therefore propose that CKS1 primarily functions within the SAM to establish boundaries between meristematic and leaf zones. Loss of gene function disrupts boundary formation, impacts phyllotactic patterns, and leads to aspects of indeterminate growth within leaf primordia. Because these perturbations arise independently of ectopic KNOX activity, the cks1 mutation defines a novel component of the developmental machinery that facilitates leaf-versus-shoot development in maize.